Draft Five Year Plan (1978-83) Part II—Statements Union Territory of Delhi - Planning Commission (Planning Commission, 1978)
Heads of development Outlay and Expenditure Sector/Agency wise Proposed Outlay Minor heads-Outlays and Expenditure Scheme wise Outlay and Expenditure Agriculture and Allied Services Cooperation Water and Power Development Industry Transport and Communication Social and Community Services
Planning Department
Planning Department